High‐Risk Youth and Their Families: A Qualitative Needs Assessment. Issue 2 (9th October 2020) - Agaskar, Vaibhavee R.; Albert, Amy; Garcia, Venessa
Abstract : This qualitative study of 36 high‐risk youth and their families identified the need for educational/career services, high quality after‐school programs, behavioral health and social services, safety and violence interventions, sports/recreational activities, and sex education.